2011
DOI: 10.5380/ce.v16i3.24227
|View full text |Cite
|
Sign up to set email alerts
|

Autonomia Profissional Do Enfermeiro: Revisão Integrativa

Abstract: A autonomia profissional do enfermeiro corresponde à realização de ações de enfermagem por meio da utilização de habilidades, conhecimentos e atitudes para tomar decisões e resolver situações no seu espaço de atuação. O objetivo deste trabalho foi verificar quais aspectos da autonomia profissional do enfermeiro estão presentes nas produções científicas brasileiras. Para isso, realizou-se uma revisão integrativa que analisou 21 artigos de língua portuguesa publicados no período de 2000 a 2009. As bases de dados… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 10 publications
1
2
0
4
Order By: Relevance
“…p =0.016) and subject's professional autonomy level. These results are congruent with many studies which indicated that working to improve expertise and involvement in training programs were found to be critical for achieving professional autonomy by promoting nurses capacity to perform and provide effective care (28,29) . These findings are not surprising due to the fact that scientific proficiency requires training program to develop autonomic experience in order to provide care and effective education to patients.…”
Section: Notsupporting
confidence: 88%
See 1 more Smart Citation
“…p =0.016) and subject's professional autonomy level. These results are congruent with many studies which indicated that working to improve expertise and involvement in training programs were found to be critical for achieving professional autonomy by promoting nurses capacity to perform and provide effective care (28,29) . These findings are not surprising due to the fact that scientific proficiency requires training program to develop autonomic experience in order to provide care and effective education to patients.…”
Section: Notsupporting
confidence: 88%
“…This result is supported with other study a descriptive correlational design aimed to describe Jordanian critical care nurses experience of autonomy in their clinical practice, which indicated that (62%) of sample were in age group of 22-30 years (19) . Another study found that the highest percent of study participant (50%) within age group (26)(27)(28)(29)(30)(31)(32)(33)(34). Data were collected by using Google form survey; whereas young individuals were the most common nurses who responded.…”
Section: Discussionmentioning
confidence: 99%
“…(SILVA et al, 2009) Moreover, each household has its singularities, which translate the way that family lives, its habits, its beliefs, and values, and that need to be understood and respected. (HERMANN;BIRTH;LACERDA, 2014) As for schooling, it is known that the female gender is economically more disadvantaged, and even with low schooling and no employment, has a higher prevalence of the outcome of this study. (WIEMANN; MUNHOZ, 2015) CMDs are associated with low schooling, poor housing conditions, low income, and participation in the productive process as a manual worker, or unemployed.…”
Section: )mentioning
confidence: 92%
“…O exercício da autonomia, no entanto, fundamenta-se em crenças do indivíduo e é influenciado por aspectos socioculturais, uma característica importante, visto que a convivência com lesões crônicas é justamente um fator de interferência nas relações sociais, laborais e até mesmo familiares (2) . O trabalho do enfermeiro que trata pacientes com feridas é compartilhado com atividades de outras categorias da saúde, porém quando o cuidado a esta clientela não é realizado de forma interdisciplinar e com fluxos bem delimitados, pode gerar impactos diretos na autonomia do enfermeiro, inclusive na tomada de decisão e resolução de problemas dentro do seu espaço de atuação/consulta de enfermagem (5) .…”
Section: Introductionunclassified